A new genus and new species of freshwater crab (Decapoda: Brachyura: Potamidae Ortmann, 1896) from Yunnan Province, China - Chu, Kelin; Zhou, Lijun; Sun, Hongying (Zootaxa, 2017)
A new genus Arquatopotamon gen. n. of the family Potamidae Ortmann, 1896, is established and a new species, Arquatopotamon jizushanense sp. n. from Yunnan Province, China is described. The new genus is established based on the distinctive distal part of the male first gonopod, with arched-shaped subterminal and terminal segments (in mesioventral view) and female gonopores (vulvae) on thoracic sternites 5/6 and a combination of characters including the carapace and male telson, while it is similar to the five known genera in Yunnan Province and adjacent area, Tenuipotamon Dai, 1990, Pararanguna Dai & Chen, 1985, Trichopotamon Dai & Chen, 1985, Potamiscus Alcock, 1909 and Aparapotamon Dai & Chen, 1985, in having a third maxilliped exopod without a flagellum. Present molecular data based on a barcoding marker of 16S rDNA provide strong support for the genus as being new.